So the general solution for the displacement z from

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: x/(k1 + k2 ), directed to the left. Therefore, keff = k1 k2 /(k1 + k2 ). Note that if k1 = 0, then keff = 0, as expected. And if k1 = ∞, then keff = k2 , as expected. 4.18. Changing k Let’s first find the new equilibrium position. If it is a distance d to the right of the center, then we have k( + d) = 3k( − d) =⇒ d = /2. The effective spring constant is k + 3k = 4k, because moving the mass a distance y to the right changes the force from the left spring by −ky , and also changes the force from the right spring by −3ky . So the general solution for the displacement, z , from equilibrium is z (t) = A cos 2 k/m t + B sin 2 k/m t . (90) The initial conditions z (0) = − /2 and v (0) = 0 quickly give A = − /2 and B = 0. So we have z (t) = −( /2) cos(2 k/m t). Adding on the /2 for the equilibrium position gives the position relative to the center as x(t) = ( /2) 1 − cos(2 k/m t) . if it were massless. Now cut the string connecting the springs. The two limp strings acquire a tension, and we now have two springs in parallel, instead of in series; see the second setup in Fig. 4. Each spring needs to support only half the weight, so each one is stretched by mg/2k. The mass therefore hangs a distance mg/2k below where it would hang if it were massless. This is 3mg/2k above where it hung before the string was cut. So the mass does indeed rise. Strange but true. 4.22. Projectile on a spring ˆ (a) The force on the projectile is F = −kr − mg y. The x component of F = ma is therefore mx = −kx =⇒ x(t) = A cos ω t + B sin ω t, with ω = k/m. And ¨ the y component is my = −ky − mg =⇒ mz = −kz , where z ≡ y + mg/k . So ¨ ¨ z takes the standard trig form, which yields y (t) = C cos ω t + D sin ω t − mg/k . The initial conditions x(0) = 0 and x(0) = v0 cos θ quickly give ˙ x(t) = v0 cos θ sin ω t. ω (94) And the initial conditions y (0) = 0 and y (0) = v0 sin θ give ˙ y (t) = mg k (cos ω t − 1) + v0 sin θ sin ω t. ω (95) (b) For small ω t, we have sin...
View Full Document

{[ snackBarMessage ]}

Ask a homework question - tutors are online